High-transmittance super-hydrophilic anti-fog antireflection film and preparation method thereof

By introducing hydrogen peroxide as a modifier during the preparation of SiO2 sol, a high-transmittance super hydrophilic anti-fog urge membrane was prepared, which solved the problem that the existing SiO2 anti-fog urge membrane is prone to fog in humid environments, and achieved a combination of high transmittance and super hydrophilic anti-fog effect.

CN119591326APending Publication Date: 2025-03-11ANHUI SCI & TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411452961.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing SiO2 amplicon membrane is prone to condensation and fogging in humid environments, resulting in a decrease in transmittance and limiting its practical application value.

Method used

During the preparation of SiO2 sol, hydrogen peroxide was introduced as a modifier, and a high transmittance ultra-hydrophilic anti-fog-enhancing membrane was prepared by reacting with anhydrous ethanol, deionized water, ammonia water and ethyl orthosilicate.

Benefits of technology

An amplicon film with a peak transmittance of more than 99.7% was achieved, and it had good super hydrophilic and anti-fogging properties, and overcame the difficulties of both transmittance and anti-fogging properties in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591326A_ABST
    Figure CN119591326A_ABST
Patent Text Reader

Abstract

The invention discloses a high-transmittance super-hydrophilic anti-fog antireflection film and a preparation method thereof, and relates to the technical field of optical thin film materials, the preparation method comprises the following steps: (1) reacting absolute ethyl alcohol, deionized water, hydrogen peroxide, ammonia water and tetraethoxysilane, and aging to obtain SiO2 sol; and (2) plating the SiO2 sol prepared in the step (1) on the surface of a glass substrate, and drying to obtain the high-transmittance super-hydrophilic anti-fog antireflection film. According to the invention, the problem that the existing antireflection film cannot have high transmittance and super-hydrophilic antifogging at the same time is solved, and the antireflection film with high transmittance and super-hydrophilic antifogging at the same time is obtained; the preparation method of the antireflection film provided by the invention has the characteristics of being simple in process, green and environment-friendly, less in required equipment, free of high-temperature treatment, low in cost, convenient to operate, easy to realize industrialization and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optical film materials, and in particular to a high-transmittance super-hydrophilic anti-fog anti-reflection film and a preparation method thereof. Background Art

[0002] Anti-reflection film, also known as anti-reflection film, is a film used to reduce surface reflection of optical components and increase the transmittance of light. It has been widely used in solar cells, solar thermal collectors, high-energy laser systems and other fields.

[0003] Commonly used methods for preparing antireflection films include phase separation, etching, oblique coating, layer-by-layer self-assembly and sol-gel. Among them, the sol-gel method has the advantages of simple operation, low cost, good uniformity of large-area film formation, and the ability to independently adjust the microstructure and chemical composition of the film. 2 It is the most commonly used antireflection film material by the sol-gel method. SiO 2 The anti-reflection film is formed by the hydrolysis and condensation of ethyl orthosilicate catalyzed by alkali. 2 Nanoparticles are randomly accumulated on the surface of the substrate. The pores between the particles reduce the refractive index of the film, making the film refractive index close to the square root of the substrate refractive index 1.23, so it has a peak transmittance of about 100%. More importantly, the anti-reflection film prepared by the sol-gel method has a higher laser damage threshold (two or three times that of other methods such as chemical deposition method) and is currently the only anti-reflection film used in high-energy laser systems. However, the SiO prepared by this method 2 There are a certain number of unhydrolyzed ethoxy groups on the surface of the antireflection film, which makes the film less hydrophilic, and the water contact angle is about 30°. During the use of this antireflection film, especially in a humid environment, condensation and fogging are prone to occur, which seriously reduces the transmittance of the antireflection film, thereby limiting its practical application value. Therefore, in the actual use of the antireflection film, its good anti-fogging properties need to be taken into account.

[0004] The film is endowed with super-hydrophilicity, so that the contact angle of water droplets on the film surface is less than 5°, and the water droplets will spread quickly on the surface, which can play a good anti-fogging effect. In order to effectively reduce the restriction of ethoxy groups on the super-hydrophilicity of the film and achieve super-hydrophilicity of the film, CSThompson et al. (Energy Materials and Solar Cells 2013, 115, 108-113) conducted a sol-gel method to form SiO 2 The antireflection film was treated at 400℃ and the ethoxy groups were removed by calcination, achieving super hydrophilic anti-fogging of the film. However, high temperature treatment is not suitable for transparent plastic substrates. Zhang Shuming et al. (Journal of Chemistry in Universities 2018, 39(6), 1342-1348) used hydrofluoric acid to treat SiO 2Etching modification of nanoparticles also achieves super-hydrophilic anti-fogging, but the refractive index of the film will also decrease due to etching, thus affecting the transmittance of the film; at the same time, the toxicity of fluorine-containing reagents and their residual problems in the film layer cannot be ignored. Therefore, under normal temperature conditions, using green and environmentally friendly methods to obtain anti-fogging and anti-reflection films with both ultra-high transmittance (>99.7%) and super-hydrophilicity is still a technical problem that needs to be solved urgently. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a high-transmittance super-hydrophilic anti-fog anti-reflection film by 2 Introducing hydrogen peroxide as a modifier during the preparation of the sol can obtain an anti-reflection film with a peak transmittance greater than 99.7%, and the anti-reflection film has good super-hydrophilic anti-fogging properties.

[0006] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0007] One of the purposes of the present invention is to provide a method for preparing a high-transmittance super-hydrophilic anti-fog anti-reflection film, comprising the following steps:

[0008] (1) Anhydrous ethanol, deionized water, hydrogen peroxide, ammonia water and ethyl orthosilicate are reacted and aged to obtain SiO 2 Sol;

[0009] (2) SiO prepared in step (1) 2 The sol is coated on the surface of a glass substrate and dried to obtain a high-transmittance super-hydrophilic anti-fog and anti-reflection film.

[0010] In the present invention, firstly, hydrogen peroxide is a weak electrolyte, which can promote the hydrolysis of the precursor and is non-toxic and harmless under normal conditions of use; secondly, the product of hydrogen peroxide introduced into the reaction system may only be water or water-based ions, free radicals, etc., which have good compatibility with the entire reaction system and will not introduce other unfriendly impurities to produce uncontrollable effects on the properties of the sol and the quality of the final film layer.

[0011] The second object of the present invention is to provide a high-transmittance super-hydrophilic anti-fog anti-reflection film prepared by the above-mentioned preparation method.

[0012] The beneficial effects of the present invention are as follows: the present invention overcomes the difficulty that the existing anti-reflection film cannot have both high transmittance and super-hydrophilic anti-fog, and obtains an anti-reflection film with both high transmittance and super-hydrophilic anti-fog; and the anti-reflection film preparation method provided by the present invention has the characteristics of simple process, green environmental protection, less equipment required, no need for high-temperature treatment, low cost, convenient operation and easy industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1The transmittance curves of the antireflection films prepared in the embodiments of the present invention and the comparative examples;

[0014] Figure 2 Schematic diagram of water contact angle of antireflection films prepared in embodiments of the present invention and comparative examples. DETAILED DESCRIPTION

[0015] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.

[0016] The present invention provides a method for preparing a high-transmittance super-hydrophilic anti-fog anti-reflection film, the preparation method comprising the following steps:

[0017] (1) Anhydrous ethanol, deionized water, hydrogen peroxide, ammonia water and ethyl orthosilicate are reacted and aged to obtain SiO 2 Sol;

[0018] (2) SiO prepared in step (1) 2 The sol is coated on the surface of a glass substrate and dried to obtain a high-transmittance super-hydrophilic anti-fog and anti-reflection film.

[0019] Furthermore, the molar ratio of anhydrous ethanol, deionized water, hydrogen peroxide, ammonia and tetraethyl orthosilicate in step (1) is (30-40):(8-12):(2-2.5):(0.15-0.18):1.

[0020] Furthermore, the reaction in step (1) is a constant temperature reaction, the reaction temperature is 25 to 30° C., and the reaction time is 1 to 6 hours.

[0021] Furthermore, the aging in step (1) is sealed aging, the aging temperature is 25 to 30° C., and the aging time is 7 to 10 days.

[0022] Furthermore, the plating in step (2) adopts the immersion-pulling method. The immersion-pulling method is a method for preparing a thin film by using the immersion and pulling process of a solution, and can prepare an anti-reflection film with high transmittance.

[0023] Furthermore, the pulling speed of the glass substrate is 500-3000 μm / s.

[0024] Furthermore, the drying is air-drying at room temperature or drying at low temperature.

[0025] The present invention provides a high-transmittance super-hydrophilic anti-fog anti-reflection film prepared by the above-mentioned preparation method.

[0026] Furthermore, the high transmittance super-hydrophilic anti-fog anti-reflection film has a thickness of 94 to 225 nm and a refractive index of 1.21 to 1.24.

[0027] Furthermore, the peak transmittance of the high-transmittance super-hydrophilic anti-fog anti-reflection film is greater than 99.7%, and the water contact angle is less than 5°.

[0028] Example 1

[0029] (1) Anhydrous ethanol, deionized water, hydrogen peroxide, ammonia water and tetraethyl orthosilicate were added into a reaction bottle in a molar ratio of 30:9.75:2.21:0.17:1, and the mixture was reacted at a constant temperature of 25°C for 2 hours, and then sealed and aged at a constant temperature of 25°C for 7 days to obtain SiO 2 Sol.

[0030] (2) Immerse the glass substrate in the SiO prepared in step (1) 2 The film was deposited in the sol at a pulling speed of 2000 μm / s and dried at room temperature.

[0031] The test results show that the antireflection film prepared in Example 1 has a refractive index of 1.22, a transmittance of 99.92% at 626 nm, and a water contact angle of 3.5°.

[0032] Example 2

[0033] (1) Anhydrous ethanol, deionized water, hydrogen peroxide, ammonia water and tetraethyl orthosilicate were added into a reaction bottle in a molar ratio of 37.6:12:2.5:0.15:1, and the mixture was reacted at 30°C for 2 hours, and then sealed and aged at 25°C for 7 days to obtain SiO 2 Sol.

[0034] (2) Immerse the glass substrate in the SiO prepared in step (1) 2 The film was deposited in the sol at a pulling speed of 500 μm / s and dried at room temperature.

[0035] The test results show that the antireflection film prepared in Example 2 has a refractive index of 1.24, a transmittance of 99.77% at 367 nm, and a water contact angle of 2.8°.

[0036] Example 3

[0037] (1) Anhydrous ethanol, deionized water, hydrogen peroxide, ammonia water and tetraethyl orthosilicate were added into a reaction bottle in a molar ratio of 40:8:2:0.18:1, and the mixture was reacted at 30°C for 2 hours, and then sealed and aged at 30°C for 10 days to obtain SiO 2 Sol.

[0038] (2) Immerse the glass substrate in the SiO prepared in step (1) 2 The film was deposited in the sol at a pulling speed of 3000 μm / s and dried at room temperature.

[0039] The test results show that the antireflection film prepared in Example 3 has a refractive index of 1.21, a transmittance of 99.89% at 797 nm, and a water contact angle of 2.5°.

[0040] Comparative Example 1

[0041] (1) Anhydrous ethanol, deionized water, ammonia water and tetraethyl orthosilicate were added to a reaction bottle in a molar ratio of 30:3.25:0.17:1, and the mixture was reacted at a constant temperature of 25°C for 2 hours, and then sealed and aged at a constant temperature of 25°C for 7 days to obtain SiO 2 Sol.

[0042] (2) Immerse the glass substrate in the SiO prepared in step (1) 2 The film was deposited in the sol at a pulling speed of 2000 μm / s and dried at room temperature.

[0043] The test results show that the antireflection film prepared in Comparative Example 1 has a refractive index of 1.21, a transmittance of 99.94% at 650 nm, and a water contact angle of 29.6°.

[0044] Comparative Example 2

[0045] (1) Anhydrous ethanol, deionized water, ammonia water and tetraethyl orthosilicate were added into a reaction bottle in a molar ratio of 37.6:9.75:0.17:1, and the reaction was carried out at a constant temperature of 25°C for 2 hours, and then the reaction was sealed and aged at a constant temperature of 30°C for 7 days to obtain SiO 2 Sol.

[0046] (2) Immerse the glass substrate in the SiO prepared in step (1) 2 The film was deposited in the sol at a pulling speed of 2000 μm / s and dried at room temperature.

[0047] The test results show that the antireflection film prepared in Comparative Example 2 has a refractive index of 1.26, a transmittance of 99.52% at 465 nm, and a water contact angle of 13.1°.

[0048] Comparative Example 3

[0049] (1) Anhydrous ethanol, deionized water, hydrogen peroxide, ammonia water and tetraethyl orthosilicate were added to a reaction bottle in a molar ratio of 40:3.25:0.74:0.17:1, and the reaction was carried out at a constant temperature of 30°C for 2 hours, and then the reaction was sealed and aged at a constant temperature of 30°C for 7 days to obtain SiO 2 Sol.

[0050] (2) Immerse the glass substrate in the SiO prepared in step (1) 2 The film was deposited in the sol at a pulling speed of 2000 μm / s and dried at room temperature.

[0051] The test results show that the antireflection film prepared in Comparative Example 3 has a refractive index of 1.22, a transmittance of 99.62% at 684 nm, and a water contact angle of 18.7°.

[0052] Depend on Figure 1 It can be seen that compared with Control Example 1, Control Example 2 increases the water content in the sol formula, and the peak transmittance of the obtained film decreases; Compared with Control Example 1, Control Example 3 uses hydrogen peroxide to treat SiO 2 The peak transmittance of the obtained film is also reduced when the sol is modified.

[0053] Depend on Figure 2 It can be seen that compared with Control Example 1, Control Example 2 increases the water content in the sol formula, and the contact angle of the film decreases, but it does not reach super hydrophilicity; Control Example 3 uses hydrogen peroxide to treat SiO 2 The contact angle of the film was reduced after the sol was modified, and it did not reach super hydrophilicity.

[0054] Therefore, Comparative Examples 1-3 show that increasing the water content alone will not only reduce the transmittance of the film, but also fail to achieve superhydrophilicity; 2 Modification of the sol will only reduce the transmittance of the film and cannot achieve superhydrophilicity.

[0055] The above embodiment controls SiO 2 The water content in the sol and the effect of hydrogen peroxide on SiO 2 The sol was modified to prepare an antireflection film with a peak transmittance greater than 99.7% and a water contact angle less than 5°.

[0056] In summary, the present invention controls SiO 2 The water content in the sol and the effect of hydrogen peroxide on SiO 2 The sol can be modified to obtain an anti-fog and anti-reflection film with both ultra-high transmittance and super-hydrophilicity.

[0057] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a high-transmittance super-hydrophilic anti-fog anti-reflection film, characterized in that: The following steps are involved: (1) reacting anhydrous ethanol, deionized water, hydrogen peroxide, ammonia water and ethyl orthosilicate, and aging to obtain SiO2 sol; (2) coating the SiO2 sol prepared in step (1) on the surface of a glass substrate and drying it to obtain a high-transmittance super-hydrophilic anti-fog and anti-reflection film.

2. The method for preparing the high transmittance super hydrophilic anti-fog anti-reflection film according to claim 1, characterized in that: The molar ratio of anhydrous ethanol, deionized water, hydrogen peroxide, ammonia and tetraethyl orthosilicate is (30-40):(8-12):(2-2.5):(0.15-0.18):

1.

3. The method for preparing the high transmittance super hydrophilic anti-fog anti-reflection film according to claim 1, characterized in that: The reaction is a constant temperature reaction, the reaction temperature is 25-30° C., and the reaction time is 1-6 hours.

4. The method for preparing the high transmittance super-hydrophilic anti-fog anti-reflection film according to claim 1, characterized in that: The aging is sealed aging, the aging temperature is 25-30° C., and the aging time is 7-10 days.

5. The method for preparing the high transmittance super-hydrophilic anti-fog anti-reflection film according to claim 1, characterized in that: The plating adopts a dipping-pulling method.

6. The method for preparing the high transmittance super-hydrophilic anti-fog anti-reflection film according to claim 5, characterized in that: The pulling speed of the glass substrate is 500-3000 μm / s.

7. The method for preparing the high transmittance super-hydrophilic anti-fog anti-reflection film according to claim 1, characterized in that: The drying is air-drying at room temperature or drying at low temperature.

8. A high-transmittance super-hydrophilic anti-fog anti-reflection film prepared by the method for preparing a high-transmittance super-hydrophilic anti-fog anti-reflection film according to any one of claims 1 to 7.

9. The high transmittance super hydrophilic anti-fog anti-reflection film according to claim 8, characterized in that: The high transmittance super-hydrophilic anti-fog anti-reflection film has a thickness of 94-225 nm and a refractive index of 1.21-1.

24.

10. The high transmittance super hydrophilic anti-fog anti-reflection film according to claim 8 or 9, characterized in that: The peak transmittance of the high-transmittance super-hydrophilic anti-fog anti-reflection film is greater than 99.7%, and the water contact angle is less than 5°.